2013
DOI: 10.1371/journal.pone.0064190
|View full text |Cite
|
Sign up to set email alerts
|

Water-Deficit Inducible Expression of a Cytokinin Biosynthetic Gene IPT Improves Drought Tolerance in Cotton

Abstract: Water-deficit stress is a major environmental factor that limits agricultural productivity worldwide. Recent episodes of extreme drought have severely affected cotton production in the Southwestern USA. There is a pressing need to develop cotton varieties with improved tolerance to water-deficit stress for sustainable production in water-limited regions. One approach to engineer drought tolerance is by delaying drought-induced senescence via up-regulation of cytokinin biosynthesis. The isopentenyltransferase g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
76
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(83 citation statements)
references
References 64 publications
6
76
0
1
Order By: Relevance
“…Under drought stress, plant CK content decreases, and the reduction in CK increases the plant responses to increasing ABA (Davies and Zhang, 1991), inducing stomata closure and inhibiting photosynthesis (Rivero et al, 2010). Our previous results suggested that the stress-induced CK synthesis, driven by a stress-induced promoter, protected against the deleterious effects of water deficit on the photosynthetic apparatus, allowing higher photosynthetic rates and higher yields after water deficit in tobacco (Rivero et al, 2009) and cotton (Gossypium hirsutum; Kuppu et al, 2013) plants grown in the greenhouse and peanut (Arachis hypogaea) plants grown under field conditions (Qin et al, 2011).…”
mentioning
confidence: 99%
“…Under drought stress, plant CK content decreases, and the reduction in CK increases the plant responses to increasing ABA (Davies and Zhang, 1991), inducing stomata closure and inhibiting photosynthesis (Rivero et al, 2010). Our previous results suggested that the stress-induced CK synthesis, driven by a stress-induced promoter, protected against the deleterious effects of water deficit on the photosynthetic apparatus, allowing higher photosynthetic rates and higher yields after water deficit in tobacco (Rivero et al, 2009) and cotton (Gossypium hirsutum; Kuppu et al, 2013) plants grown in the greenhouse and peanut (Arachis hypogaea) plants grown under field conditions (Qin et al, 2011).…”
mentioning
confidence: 99%
“…Similar results were also reported in IPT transgenic cotton (Kuppu et al, 2013), peanut (Qin et al, 2011) and tobacco (Rivero et al, 2010) with reduced water supply.…”
supporting
confidence: 87%
“…Delayed senescence, increased biomass, increased chlorophyll content and photosynthetic rates (Kuppu et al, 2013) …”
Section: Tobacco (Nicotiana Tabacum)mentioning
confidence: 99%
See 1 more Smart Citation
“…The determination of the function of an observed response is one of the most complex issues in plant stress biology. In trying to understand responses to stresses involving a water deficit component, many genes induced by periods of water deficit have been identified and characterized [3][4][5]. In an unfavorable environment, plants must withstand multiple abiotic and biotic stresses, and a response observed during one type of stress may in fact have a role in the amelioration of another condition [6].…”
mentioning
confidence: 99%